118 Real world implementation of an evidence-based home cardiac rehabilitation programme for people with heart failure and their caregivers: findings from the scot:reach-hf study. (6th June 2022) - Purcell, Carrie; Taylor, Rod; Cleland, John; Cowie, Aynsley; Dalal, Hasnain; Ibbotson, Tracy; Murphy, Clare
Abstract : Introduction: Despite evidence that cardiac rehabilitation (CR) and self-care are essential in managing heart failure, and strong national and international guidelines recommending their provision, referral and uptake remains low. Centre-based provision is a known barrier, and the need for flexible models of CR has become more pronounced in the recent pandemic context. In a multicentre randomised controlled trial of the REACH-HF home-based self-management support programme for HFrEF demonstrated its clinical and cost-effectiveness. However, full understanding of its implementation is needed to inform scaled roll-out in a 'real world' NHS setting. The SCOT:REACH-HF study aimed to 1) compare outcome improvements with those identified in the RCT, 2) identify facilitators of and barriers to real-world implementation, and 3) estimate of the economic impact of implementation. Methods: We conducted a mixed-method implementation study of the delivery of REACH-HF in across NHS Scotland in 2021–22. Health professionals were trained to facilitate delivery of the 12-week programme to people with heart failure and a nominated 'caregiver' where applicable. Patient and caregiver outcomes assessed at baseline and four-month follow-up included the Minnesota Living with Heart Failure Questionnaire, EQ-5D-5L, Hospital Anxiety and Depression Scale, Health Literacy Questionnaire, and Caregiver Burden Questionnaire. Qualitative interviews were conducted with key health professionals and stakeholders, and analysis of broader contextual implementation data was also incorporated. Results and Conclusions: We recruited 136 people with HFrEF in six health board areas (NHS Ayrshire and Arran, Lanarkshire, Forth Valley, Highland, Orkney and Shetland) serving urban and rural populations. Of those, 124 completed baseline, 113 completed REACH-HF, and 99 completed 4-month follow-up. 47 participants brought caregivers into the study, with 29 of those completing the programme, and 20 completing follow-up. Semi-structured interviews were conducted with 11 trained REACH-HF facilitators, five supporting team members/managers, and four national stakeholders. We will report changes seen in patient and caregiver outcomes following participation in REACH-HF, present barriers and facilitators identified in the qualitative interviews, and discuss implications for the wider implementation and sustainability of the REACH-HF programme. Conflict of Interest: None